Development of Computer-Based Learning Media on Collision Lesson Using the Context of Traditional Marbles Game - Furqon, Imam; Afgani, Muhammad Win; Putri, Jamiatul Khairunnisa; Suhadi; Mabruroh, Faizatul (Schrödinger: Journal of Physics Education, 2024)
Purpose of the study: This research aims to develop learning media using computer-based collision material in the context of the traditional game of marbles. Methodology: This research is a Research and Development study using the ADDIE research design. The research was conducted at MA Al-Fatah Palembang using instruments in the form of interviews and questionnaires for data collection. Interviews were conducted with physics subject teachers at MA Al-Fatah Palembang. The questionnaire was given to media expert validators, material expert validators, teachers and students to see the validity and practicality of media use. Main Findings: The result of this research is a learning media product using computer-based collision material in the context of the traditional game of marbles which meets the valid and practical criteria. The results of media expert validation that have been carried out show percentages of 91,7% with very valid categories. The material expert validation results show a percentage of 92.8% with a very valid category. The results of the limited trial showed that the percentage of assessments from physics subject teachers was 89,2% in the very practical category and students' responses to the use of learning media showed a percentage of 87.3% in the very practical category. Novelty/Originality of this study: The main novelty of this study lies in utilizing a traditional game as a contextual and engaging framework to teach abstract physics concepts, such as collisions, in a more comprehensible way.